Application of fitting parameters in best fit equation - Qian, Zhai (2019)
Soil-water characteristic curve (SWCC) contains key information for the application of unsaturated soil mechanics principles to engineering practice. SWCC variables such as air-entry value, residual suction and residual saturation are commonly referred to for estimation of other unsaturated soil properties. Though there are clear definitions for these SWCC variables, it is difficult to measure them directly in laboratory and these SWCC variables are commonly estimated from SWCC. Hydraulic conductivity of unsaturated soil is the major property that controls water flow in soil. The laboratory measurement of hydraulic conductivity is time consuming and costly. Therefore, hydraulic conductivity is also commonly estimated from SWCC. Normally, SWCC is represented by a best fit equation which is typically governed by few fitting parameters. These fitting parameters can be obtained from a best fit procedure and are proven to be dependent on each other. Fredlund and Xing’s (1994) equation is one of the popular equations commonly used by researchers and there are only three fitting parameters such as “a”, “n”, “m” in this equation. Correlation equations between SWCC variables, hydraulic conductivity and the fitting parameters such as “a”, “n” and “m” are presented in this paper. In addition, the variability in the determined SWCC variables and hydraulic conductivity due to the variation in these fitting parameters is also discussed in this paper.